(untitled) (Sains Humanika, 2018)
Organizational citizenship behavior and task performance is an integral part of job performance. This study aims to examine the relationship between job satisfaction, organizational commitment, organizational citizenship behavior and task performance. In addition, this study aims to examine the role of organizational citizenship behavior as a mediator linking job satisfaction and organizational commitment to task performance among academicians in a higher learning instutution. A total of 211 respondents participated in this study. Four instruments were used, namely job satisfaction questionnaire, organizational commitment questionnaire, organizational citizenship behavior scale and task performance scale developed by the researchers. Results showed that there was a significant correlation between job satisfaction, organizational commitment and organizational citizenship behavior with task performance. Results of multiple regression showed that organizational citizenship behavior significantly mediated the relationship between organisational commitment and task performance. The study also found that organizational citizenship behavior did not mediate the link between job satisfaction and task performance among academic staff. Implication of the study indicate the important of job satisfaction, organizational commitment and organizational citizenship behavior in influencing organization effectiveness dan performance.